DECONSTRUCTION OF CARTESIAN DUALISM IN SENSORY PERCEPTION - Diaz Supandi, Muhammad; Elit Ave Hidayatullah (Universitas Kiai Abdullah Faqih Gresik, 2025)
Abstract:This study aims to deconstruct Cartesian dualism, which has dominated Western epistemology, particularly in understanding the relationship between the mind, body, and sensory perception, leading to a passive and mechanical view of perception. The research offers a solution from the perspective of holistic Islamic epistemology, grounded in the concept of tawhid (oneness). The main objectives are: (1) to critically analyze the tension between Cartesian dualism and Islamic epistemology using maq??id? exegesis of Qur'anic verses, (2) to formulate an alternative framework based on Islamic tur?th, known as